The Effect of the Chin-cap Treatment on the Growth and Development of the Upper Jaw for the Individuals with Skeletal Class 1 pattern - Neslihan Üçüncü Karabekir; Sema Yüksel Ilgar (Turkish Journal of Orthodontics, 1988)

(untitled)
“The Effect of the Chin-cap Treatment on the Growth and Development of the Upper Jaw for the Individuals with Skeletal Class 1 pattern.” In this longitudinal Study, the effect of chin-cap treatment on the growth and development of the upper Jaw for the individuals having skeletal Class 1 pattern with anterior crossbite has been investigated. The control group consist of 12 individuals having an average chronological age of 8 years 3 months and the research group with 10 individuals having an average chronological age of 8 years 7 months. Two lateral caphalometric films were taken from each of these individuals at the beginning and end of the research. In these films, many measurement relating to angles and dimensions for upper jaw were taken. At the end of one year, significant increase on the dimension of N—ANS, G—PNS and I—NA were observed on the control group. On the other hand significant increase on the dimension of N—ANS, M—ANS, G—PNS, I—NA and angles of ANB and I—NA were found on the research group. In this study, It can be concluded that cnip-cap used for the treatment of individuals having skeletal class 1 pattern with anterior cross-bite has no significant effect on the vertical dimension and sagittal measurments, except for the angles of ANB and l—NA